EFFECT OF LIQUID PHASE ON THE STRUCTURE FORMATION OF CAST ALLOY Al-11,7% Si - A. I. Anikin; T. R. Gilmanshina; V. I. Anikina; A. A. Kovaleva; N. A. Babitsky; A. Yu. Semusheva (Литьë и металлургия)
The influence of a thixotropic heat treatment on the structure formation of the eutectic aluminum-silicon alloy subject to the temperature and time of exposure near the eutectic equilibriumis giver in the article. The theoretical study of the process based on the data obtained and the thermal analysis of microstructures is made and described.